Rectal cancer: French Intergroup clinical practice guidelines for diagnosis, treatments and follow-up (SNFGE, FFCD, GERCOR, UNICANCER, SFCD, SFED, SFRO). Issue 4 (April 2017) - Gérard, Jean-Pierre; André, Thierry; Bibeau, Frédéric; Conroy, Thierry; Legoux, Jean-Louis; Portier, Guillaume; Bosset, Jean-François; Cadiot, Guillaume; Bouché, Olivier; Bedenne, Laurent; ,
Abstract: Introduction: This document is a summary of the French Intergroup guidelines regarding the management of rectal adenocarcinoma published in February 2016. Method: This collaborative work, under the auspices of most of the French medical societies involved in the management of rectal cancer, is based on the previous guidelines published in 2013. Recommendations are graded into 3 categories according to the level of evidence of data found in the literature. Results: In agreement with the ESMO guidelines (2013), non-metastatic rectal cancers have been stratified in 4 risk groups according to endoscopy, MRI or endorectal-ultrasonography. Locally-advanced tumors are limited to groups 3 and 4 (T3 ≥4 cm or T3c–d or N1-2 or T4). These tumors are usually treated using neoadjuvant treatment and total proctectomy (TME). Adjuvant treatment depends on the pathological findings. Very early (group 1) or early (group 2) tumors are managed mainly by surgery, and organ preservation may be an option in selected cases. For metastatic tumors, the recommendations are based on less robust evidence and chemotherapy plays a major role. Conclusion: Such recommendations are constantly being optimized and each individual case must be discussed within a Multi-Disciplinary Team.